Analysis of Mosul and Haditha Dam Flow Data (Journal of Engineering, 2014)
The expansion in water projects implementations in Turkey and Syria becomes of great concern to the workers in the field of water resources management in Iraq. Such expansion with the absence of bi-lateral agreement between the three riparian countries of Tigris and Euphrates Rivers; Turkey, Syria and Iraq, is expected to lead to a substantially reduction of water inflow to the territories of Iraq. Accordingly, this study consists of two parts: first part is aiming to study the changes of the water inflow to the territory of Iraq, at Turkey and Syria borders, from 1953 to 2009; the results indicated that the annual mean inflow in Tigris River was decreased from 677 m3/sec to 526 m3/sec, after operating Turkey reservoirs, while in the Euphrates River the annual mean inflow was decreased from 1006 m3/sec to 627m3/sec after operating Syria and Turkey reservoirs. Second part is forecasting the monthly inflow and the water demand under the reduced inflow data. The results show that the future inflow of the Tigris River is expected to decrease to 57%, and reaches 301m3/sec. The Mosul reservoir will be able to supply 64% only of the water requirements to the downstream. The share of Iraq from the inflow of the Euphrates River is expected to be 58%, therefore the future inflow will reach 290 m3/sec. The Haditha reservoir will be able to supply 46% only of the water requirements to the downstream, due to reduced inflow at Iraqi border in the future.